The letters are lost! - Ernst, Lisa Campbell (New York, N.Y., U.S.A. : Viking, 1996)
Long ago all the letters of the alphabet were together in their box, but one by one they disappeared and now the reader helps to find them.
G1
Keywords: Lost and found possessions -- Fiction; Alphabet